Antibody Targets on the Surface of Plasmodium falciparum–Infected Erythrocytes That Are Associated With Immunity to Severe Malaria in Young Children. (26th October 2018) - Chan, Jo-Anne; Boyle, Michelle J; Moore, Kerryn A; Reiling, Linda; Lin, Zaw; Hasang, Wina; Avril, Marion; Manning, Laurens; Mueller, Ivo; Laman, Moses; Davis, Timothy; Smith, Joseph D; et al.
Abstract: Background: Sequestration of Plasmodium falciparum –infected erythrocytes (IEs) in the microvasculature contributes to pathogenesis of severe malaria in children. This mechanism is mediated by antigens expressed on the IE surface. However, knowledge of specific targets and functions of antibodies to IE surface antigens that protect against severe malaria is limited. Methods: Antibodies to IE surface antigens were examined in a case-control study of young children in Papua New Guinea presenting with severe or uncomplicated malaria (n = 448), using isolates with a virulent phenotype associated with severe malaria, and functional opsonic phagocytosis assays. We used genetically modified isolates and recombinant P. falciparum erythrocyte membrane protein 1 (PfEMP1) domains to quantify PfEMP1 as a target of antibodies associated with disease severity. Results: Antibodies to the IE surface and recombinant PfEMP1 domains were significantly higher in uncomplicated vs severe malaria and were boosted following infection. The use of genetically modified P. falciparum revealed that PfEMP1 was a major target of antibodies and that PfEMP1-specific antibodies were associated with reduced odds of severe malaria. Furthermore, antibodies promoting the opsonic phagocytosis of IEs by monocytes were lower in those with severe malaria. Conclusions: Findings suggest that PfEMP1 is a dominant target of antibodies associated with reduced risk of severe malaria, and function in part by promoting opsonic phagocytosis. Abstract : Antibodies to surface antigens of infected erythrocytes are associated with resistance to severe malaria in children, and target PfEMP1 and promote opsonic phagocytosis by monocytes.